2021
DOI: 10.1021/acs.jafc.1c01908
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms Mediating the Protective Effects ofTricholoma matsutake-Derived Peptides in Mitigating DSS-Induced Colitis

Abstract: Intestinal barrier dysfunction and inflammatory cytokine secretion play crucial roles in inflammatory bowel disease (IBD). Herein, we investigated the protective effects of Tricholoma matsutake-derived peptides SDIKHFPF and SDLKHFPF against dextran sulfate sodium-induced colitis. Both peptides alleviated colitis signs, including diarrhea, weight loss, bloody stools, colon shortening, and histopathological changes, while reducing mucus destruction, goblet cell exhaustion, and intestinal permeability. SDIKHFPF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 51 publications
(94 reference statements)
5
34
0
Order By: Relevance
“…These multifaceted effects confirmed the anti-inflammatory effect of T. matsutake peptides, which is consistent with the results of a previous report . Collectively, T.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These multifaceted effects confirmed the anti-inflammatory effect of T. matsutake peptides, which is consistent with the results of a previous report . Collectively, T.…”
Section: Discussionsupporting
confidence: 92%
“…DLPU2021036). After a week of acclimatization, 50 mice were equally and randomly assigned to five groups: control group treated with sterile water, gastric injury model group treated with ethanol, lansoprazole (30 mg/kg body weight [BW])-treated positive control group, and peptides SDLKHFPF (50 mg/kg BW) and SDIKHFPF (50 mg/kg BW)-treated groups. , T. matsutake peptides SDLKHFPF and SDIKHFPF were orally administered on days 1–14 as described by Wang et al ., and lansoprazole were orally administered on days 8–14; the mice were fasted for 24 h before the last administration (Figure A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Moreover, a previous study has demonstrated that the increase in MPO activity in colon tissues was generally accompanied by an increased inflammation level, and therefore as a biomarker of inflammation in mice with DSS-induced colitis. 10 Our research suggested both the EGT-4 μg group and the EGT-40 μg group significantly prevented the DSS-induced activation of MPO activity in colon tissues ( Figure 5 A), which confirmed the previous observation that EGT inhibited MPO activity in vitro. ( 15 )…”
Section: Discussionsupporting
confidence: 89%
“… 5 At present, the current effective treatment strategies for UC patients are surgery and medical therapy, which usually induce a series of complex side effects. In recent years, food-derived functional ingredients as the adjuvant treatment for UC have been gradually investigated and it is shown that dietary polysaccharides, 6 , 7 conjugated linoleic acid, 8 phenolic compounds, 9 and peptides 10 , 11 can relieve colitis by inhibiting inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%